An Investigation into the Integration of Local Wisdom and Natural Dye Extraction in Contemporary Art Education through Creative Hand-Stitched Textile Practices - Tonthongkam, kengkard; Sanserm, Siriwat; Charoensuk, Patiphan (Journal of Humanities and Social Sciences Nakhon Pathom Rajabhat University, 2026)
This article presents a contemporary art teaching approach based on local wisdom, integrating hand-woven textile crafts with natural dye extraction from community plants. The goal is to develop an “integrated contemporary art learning model” that not only emphasizes creativity but also aligns with cultural concepts, sustainability, and educational innovation. The proposed learning model is based on a process that relates analytical thinking, design, and practical learning through hand-woven textiles and natural dyes. It comprises four main components: 1) creativity that emphasizes the translation of concepts into art; 2) contemporary art dimensions that connect social issues with local materials; 3) integration of hand-woven textile crafts to reflect local identity; and 4) learning management to develop contemporary art innovations, using community-based learning and promoting critical thinking within the cultural context of students. The learning activities include exploring local wisdom, extracting and experimenting with local plant dyes, sewing to create contemporary artworks, and displaying works in creative exhibitions, both in real-world and digital media. The focus is on enabling students to create “new value” for the community’s cultural capital through contemporary interpretation and communicating social ideas. The expected learning outcomes include the development of creativity and critical design, the enhancement of concentration and refined skills, collaboration, and an understanding of cultural values. This approach aligns with the Sustainable Development Goals (SDGs), both in terms of educational quality and cultural preservation.